2016
DOI: 10.7717/peerj.2799
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Mother, ActiGraph wGT3X-BT, and a hand tally for measuring steps at various walking speeds under controlled conditions

Abstract: IntroductionWalking is endorsed as health enhancing and is the most common type of physical activity among older adults. Accelerometers are superior to self-reports when measuring steps, however, if they are to be used by clinicians the validity is of great importance. The aim of this study was to investigate the criterion validity of Mother and ActiGraph wGT3X-BT in measuring steps by comparing the devices to a hand tally under controlled conditions in healthy participants.MethodsThirty healthy participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Given our results, the iPhone SE, including the apps Health, Accupedo, Pacer, and Runtastic Pedometer, and the Garmin Vivofit 2 are suitable tools for step counting in healthy young as well as middle‐aged individuals. Because these devices demonstrated a higher validity compared to the widely used ActiGraph wGTX+ especially at slow walking speeds, thereby confirming previous findings, they may be a promising alternative for step counting, for example, in patients with chronic diseases and severely reduced ambulatory abilities to monitor adherence to PA‐related therapy recommendations such as step goals. In this context, the phone may be placed in a backpack or shoulder bag for accurate step counting and does not necessarily have to be carried in the pants pocket, thus substantially improving the versatility for objective PA assessment in large‐scale clinical as well as research settings.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Given our results, the iPhone SE, including the apps Health, Accupedo, Pacer, and Runtastic Pedometer, and the Garmin Vivofit 2 are suitable tools for step counting in healthy young as well as middle‐aged individuals. Because these devices demonstrated a higher validity compared to the widely used ActiGraph wGTX+ especially at slow walking speeds, thereby confirming previous findings, they may be a promising alternative for step counting, for example, in patients with chronic diseases and severely reduced ambulatory abilities to monitor adherence to PA‐related therapy recommendations such as step goals. In this context, the phone may be placed in a backpack or shoulder bag for accurate step counting and does not necessarily have to be carried in the pants pocket, thus substantially improving the versatility for objective PA assessment in large‐scale clinical as well as research settings.…”
Section: Discussionsupporting
confidence: 78%
“…The ActiGraph worn on the hip was only accurate for treadmill walking speeds of 4.8 and 6.0 km/h. The detected magnitude of the deviation of 23.8% from the gold standard at 3.2 km/h is comparable to the 26.7% deviation Riel et al 24 found in healthy college students (mean age 27.9 years) and thus clearly questions the suitability of the ActiGraph to be used for step detection in slow walking speeds. In addition, the confirmed inaccuracy of the hip-worn ActiGraph seriously contests the use of this device as the reference method for step counting during activities of daily life and thus puts even most recent research findings 37 into question.…”
Section: Role Of Device Position and Clinical Relevance Of Deviatiosupporting
confidence: 61%
See 1 more Smart Citation
“…A recent technical assessment of activity trackers’ accuracy has documented that affordable consumer trackers can compete with advanced medical products when it comes to accuracy. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The protocol may have caused these low accuracies: movement speeds were self-selected when subjects conducted the above four activities. If these activities had instead been performed on a treadmill or paced at a preset speed ( Harrell et al, 2005 ; Riel et al, 2016 ), classifications may have been more distinct; however, treadmill speeds do not represent the innate characteristics or real physical activities performed by children in daily life. It was observed that some participants walked at equal speeds during WS and WF activities, whereas others ran too fast during the RS protocol.…”
Section: Discussionmentioning
confidence: 99%